The rise of a new media ecosystem: exploring 15M's educommunicative legacy for radical democracy. - Barbas, Ángel; Treré, Emiliano (Social Movement Studies, 2023)
This article explores the influence that the educommunicative dimension of the 15M Movement has had on the creation and consolidation of a new ecosystem of independent media. To this end, we rely on a document analysis of the movement's minutes and manifestos and on the review of the editorial principles and educational activities of a sample of independent media. We also draw on ten in-depth interviews with key journalists and activists who actively participated in the 15M. We argue that the movement's media activism had a clear educommunicative orientation that strengthened pre-existing media activism, opening windows of opportunity for media innovation. This contributed to the rise of a new media ecosystem of independent media characterised by three key elements: (1) synergies and mutual support; (2) the key role of the community of subscribers and users; and (3) an educational agency with a public service orientation. Finally, we illustrate that this new media ecosystem displays a clear educommunicative orientation. This orientation is rooted in the imaginary and practices of the 15M and is based on the revitalised civic role of journalism and on the value of information for radical democracy. This article advances social movement studies by engaging a dialogue between an educommunicative perspective and a media ecology lens. It articulates the relevance of media as educational agents and explores the impact of a social movement in the creation and shaping of a new media ecosystem.